2022
DOI: 10.3390/life12081140
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on the Anti-Cancer Effects of Oleuropein

Abstract: In Mediterranean cuisine and culture, olive oil and olive fruits play a significant role. Many people believe that those who consume olive oil and its fruit live longer and have a decreased risk of illness. Olive leaves were used to treat a range of diseases in ancient times, including malaria fever and lower earaches. Although it was not understood at the time what key components were responsible for these effects because they had not yet been discovered, Oleuropein is now recognized as one of the primary ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 80 publications
1
22
0
Order By: Relevance
“…25 Some research works have shown that oleuropein has apoptotic effects in different cancer cell lines. 26 Vizza et al reported that the extract obtained from olive leaf, which is rich in polyphenols, induced apoptosis in the HeLa cells due to an increased expression of p21. 27 On…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Some research works have shown that oleuropein has apoptotic effects in different cancer cell lines. 26 Vizza et al reported that the extract obtained from olive leaf, which is rich in polyphenols, induced apoptosis in the HeLa cells due to an increased expression of p21. 27 On…”
Section: Discussionmentioning
confidence: 99%
“…Some research works have shown that oleuropein has apoptotic effects in different cancer cell lines 26 . Vizza et al.…”
Section: Discussionmentioning
confidence: 99%
“…OL is recognized as the most abundant phenolic of OLE [ 37 ]. The anticancer effect of OL as an antiproliferative and an apoptosis promoter was previously demonstrated in multiple cancer types, such as breast and colon cancer cell lines [ 38 , 39 , 40 , 41 ]. Additionally, our previous study showed that an equal concentration of OL-only from a predetermined amount of OLE (15%) demonstrated an anticancer effect in T98G cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oleuropein (Oleu) is the principal phenolic component present in olive leaves, in addition to other essential components, i. e., rutin, catechin, tyrosol, and caffeic acid [9,10] . Oleu has a wide range of anti‐inflammatory, anti‐microbic, antioxidant, and immunomodulatory activities [11] . A number of studies have shown that the consumption of Oleu decreases cancer incidence, especially in the stomach, breast, and colorectal cancer, due to its antioxidant property [12] .…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Oleu has a wide range of anti-inflammatory, anti-microbic, antioxidant, and immunomodulatory activities. [11] A number of studies have shown that the consumption of Oleu decreases cancer incidence, especially in the stomach, breast, and colorectal cancer, due to its antioxidant property. [12] However, recent studies have shown that the effects of Oleu on cancer go beyond that, where it acts as a both anti-proliferative and apoptotic promoter in a number of cancer cells.…”
Section: Introductionmentioning
confidence: 99%